The final meltdown of dead-ice at the Holocene Thermal Maximum (8500–7400 cal. yr BP) in western Latvia, eastern Baltic. (August 2017) - Stivrins, Normunds; Liiv, Merlin; Heinsalu, Atko; Gałka, Mariusz; Veski, Siim
It is commonly assumed that the majority of buried ice-blocks in Europe melted at the end of Late Glacial period and during the first part of the early-Holocene. We show, however, that scattered dead-ice-blocks may have been preserved in the ground until 8500 cal. yr BP. We analysed thermokarst features in Lake Ķikuru, western Latvia, by means of a multi-proxy approach (pollen, non-pollen palynomorphs, plant macrofossils, diatoms, loss-on-ignition, magnetic susceptibility, C:N ratio, carbon accumulation rate and radiocarbon dating). Abiotic and biotic processes following the ice-block meltdown suggests abrupt development of a thermokarst from 8500 to 7400 cal. yr BP. Important changes in local vegetation occurred with the deepening of a kettle-hole during the transition from a fen to a lake that nearly coincided with the appearance of the first fish at 7800 cal. yr BP, thus forming a clear indication of a lacustrine environment. Our study shows that a thin peat layer formed at first and, due to the meltdown of the ice-block, it gradually lowered to the bottom of the kettle-hole, and gyttja begun to accumulate afterwards. Given that thermokarst arise when the mean summer air temperature gradually increases to a value above the present-day temperature, we must assume that the local conditions must have been exceptional to secure ice-block from the meltdown for so long. Therefore, the legacy of the last ice age was still evident even ca. 5500 years after the Weichselian ice retreat from the eastern Baltic.